The Clinical Pharmacist-Led Consultation for Infectious Diseases in Guizhou Province, China: A Survey Among Hospital Pharmacies - Zhang, Jiaxing; Xu, Chang; Zheng, Wenyi; He, Rui; Xie, Juan; Qian, Xin; Xiong, Shijuan; Chen, Qi (Frontiers in Pharmacology, 2020)
Background: As antimicrobial resistance became an increasing threat to global public health, Clinical Pharmacist-led Consultation (CPC) for Infectious Diseases (ID) was developed in China. We conducted a survey among hospital pharmacies to investigate the present situation and potential determinants of CPC for ID in China’s Guizhou Province. Methods: The study was conducted by sending the questionnaire to the directors of hospital pharmacy who were members of Guizhou Province Pharmaceutical Administration Collaboration Network (GPPACN) from April to May 2019. We implemented the Firth’s logistic regression model to analyze the factors that influence the implementation of CPC. The acceptance rate of consultation suggestions (ARCS) and effective response rate after acceptance of pharmacists’ suggestions (ERRAPS) were pooled by meta-analysis using a random effect model, respectively. A pairwise meta-analysis was performed to compare the effective response rate between patients whose treatment followed the pharmacists’ suggestions and those whose treatment did not. Results: A total of 83 hospitals covering 9 regions in Guizhou Province were included in this survey. The results showed that 50 hospitals (60.24%) developed the CPC for ID. Staffing ID, respiratory, or general clinical pharmacist had a significantly positive effect on the implementation of CPC (Adjusted Odds Ratios = 7.298, 95% CI (Confidence Interval): 2.232 to 23.858). The pooled ARCS and ERRAPS for secondary hospitals were 97.59% (95%CI: 94.27% to 100.00%) and 88.36% (95%CI: 84.71% to 92.17%), respectively. Importantly, CPC improved the prognosis of ID patients (Risk Ratio (RR) =6.49, 95%CI: 2.84 to 14.82) in these hospitals. Conclusion: CPC adoption is gradually increasing among hospitals and will be a promising intervention for ID treatment at grassroots medical institutions in Guizhou Province. Training more clinical pharmacists to specialize in ID, respiratory, or general diseases might be the most practical measure to promote the development of CPC for ID.